Pencegahan Stunting melalui Peningkatan Gizi Ibu Hamil dan Anak Balita di Desa Perlis Kabupaten Langkat - Puspa Sari; Maimunah Maimunah; Chentia Misse Isabella (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Stunting remains one of the major public health challenges in Indonesia, including in Perlis Village, Langkat Regency. This community service program aimed to improve knowledge, awareness, and nutritional practices among pregnant women and families as an effort to prevent stunting. The implementation was divided into three stages: preparation, implementation, and evaluation. Activities included baseline surveys, nutrition education through counseling and workshops, regular nutrition classes, provision of supplementary foods, and collaboration with local farmers to ensure access to nutritious food sources. The results of the program showed a significant increase in pregnant women’s nutritional knowledge from 40% to 80%, positive changes in dietary patterns with 70% of participants reporting increased consumption of fruits and vegetables, and improved awareness of stunting from 30% to 75%. In addition, access to local nutritious food sources became more available through community partnerships. In conclusion, nutrition education integrated with the utilization of local food resources can enhance family understanding and dietary practices, thus potentially reducing the risk of stunting. It is recommended that similar programs be implemented sustainably with cross-sectoral support to strengthen community nutritional resilience.